Decompressive Craniectomy for Malignant Middle Cerebral Artery Stroke - Landreneau, Mark M.; Sheth, Kevin N. (Seminars in Respiratory and Critical Care Medicine, 2017)
Advancements in the treatment of ischemic stroke have led to a recent decline in overall stroke mortality, but patients with hemispheric infarcts remain at high risk for death. Recent advances in the approach to this devastating disease include early identification of patients at high risk for swelling and standardized approaches to medical therapy. However, surgical decompression continues to be the most effective treatment for malignant edema from large hemispheric strokes. Patient selection in the past had been strictly limited to younger ages and the nondominant hemisphere. More recent evidence demonstrates a mortality benefit in older patients with a limited impact on morbidity. Judicious patient selection and shared, informed decision making with families remain the optimal approach for this devastating disease.
Keywords: Decompressive Craniectomy; decompressive hemicraniectomy; malignant; ischemic stroke; middle cerebral artery stroke; hemispheric stroke; malignant edema; surgical decompression; stroke edema